Beasts and boundaries: An introduction to animals in sociology, science and society - Hobson-West, Pru (Qualitative Sociology Review, 2007)
Traditionally, sociology has spent much more time exploring relationships between humans, than between humans and other animals. However, this relative neglect is starting to be addressed. For sociologists interested in human identity construction, animals are symbolically important in functioning as a highly complex and ambiguous “other”. Theoretical work analyses the blurring of the human-animal boundary as part of wider social shifts to postmodernity, whilst ethnographic research suggests that human and animal identities are not fixed but are constructed through interaction. After reviewing this literature, the second half of the paper concentrates on animals in science and shows how here too, animals (rodents and primates in particular) are symbolically ambiguous. In the laboratory, as in society, humans and animals have unstable identities. New genetic and computer technologies have attracted much sociological attention, and disagreements remain about the extent to which humananimal boundaries are fundamentally challenged. The value of sociologists’ own categories has also been challenged, by those who argue that social scientists still persist in ignoring the experiences of animals themselves. This opens up notoriously difficult questions about animal agency. The paper has two main aims: First, to draw links between debates about animals in society and animals in science; and second, to highlight the ways in which sociologists interested in animals may benefit from approaches in Science and Technology Studies (STS).